Social Guarantees in the Case of Employees’ Dismissal in Russia Comparative Legal Aspects of Russian and Foreign Labor Law - Zavgorodniy, Alexander (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The main purpose of the article is to identify the contradictions and problems arising when both international labor standards and Russian labor law are applied and separate guarantees to workers are provided in the case of their dismissal. The object of the research is the employment relationship which arises between the employer and the employee when social guarantees are given to the workers when the employment relations are terminated. This article considers the regulations of Russian and foreign labor law which provide workers with certain guarantees if the employment contract is terminated at the initiative of the employer. For the first time, these guarantees are considered from a comparative legal perspective. Specific recommendations about improvement of the Russian labor law and its enforcement.